Oscillation of the orientation of cardiomyocyte aggregates in human left ventricle free wall. Issue 3 (17th November 2022) - Wang, Shunli; Cui, Junning; Jing, Yuhan; Varray, François
Abstract: Orientation of local cardiomyocyte aggregates in the human left ventricle free wall experiences an oscillation in the laminar structure regions, besides its gradual change trend. We described this oscillation using five transmural samples imaged at the European Synchrotron Radiation Facility with an isotropic voxel size of 3.5 × 3.5 × 3.5 μm 3 . In the reconstructed volume of each sample, we manually selected a region containing a regular laminar structure as the region of interest and measured the distribution of the orientation of local cardiomyocyte aggregates inside using a Fourier‐based method. Then, we extracted the gradual change part of the orientation of cardiomyocyte aggregates with a three‐dimensional centered Gaussian filter and measured the angle between the original orientation vector of local cardiomyocyte aggregates and its gradual change part. Further, we assessed the measured angles in different local coordinates. The results indicate that the oscillation amplitude of the orientation of cardiomyocyte aggregates is regional in the left ventricle wall, which may promote our understanding of the rearrangement mechanism of the cardiomyocyte aggregates and provide a new biomarker to study the heart physiological status. Abstract : Beside the gradual change trend, the orientation of local cardiomyocyte aggregates also experiences an oscillation in the laminar structure regions. The twist of the orientation of cardiomyocyte aggregates mainly happen in the planes approximate parallel to the local aggregations. The oscillation amplitude is regional.